2016
DOI: 10.1055/s-0036-1584918
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Psoriatic Arthritis: A Multiparametric Analysis Using Imaging Technique and Laboratory Markers of Inflammation and Vascular Function

Abstract: Cardiovascular disease is one of the leading causes of death in psoriatic arthritis (PsA). Pathogenesis of accelerated atherosclerosis in PsA remains to be elucidated. Endothelial dysfunction (ED) often precedes manifesting atherosclerosis. This study aims to assess carotid intima-media thickness (CIMT), a marker of atherosclerosis in PsA, in context of markers of inflammation and vascular function. A cross-sectional study was performed in 18 PsA patients who were compared with 18 controls matched for age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
4
9
1
2
Order By: Relevance
“…Similarly to our study, Gonzalez-Juanatey et al demonstrated there was no significant correlation between ESR, CRP and CIMT [14]. Garg et al observed no correlation between ESR, CRP, IL-1 and CIMT although CIMT was positively correlation with IL-6 [47].…”
Section: Discussionsupporting
confidence: 84%
“…Similarly to our study, Gonzalez-Juanatey et al demonstrated there was no significant correlation between ESR, CRP and CIMT [14]. Garg et al observed no correlation between ESR, CRP, IL-1 and CIMT although CIMT was positively correlation with IL-6 [47].…”
Section: Discussionsupporting
confidence: 84%
“…So far, several studies have investigated factors suspected of being associated with an increased cardiovascular risk and with disease activity in patients with PsA. Among the most indicated factors were ESR, CRP [29,31], proinflammatory cytokines (TNF, IL-17, IL-1β) [32][33][34], and particular clinical symptoms such as peripheral arthritis and dactylitis [31,35]. Interestingly, none of these factors seemed to be connected directly to a highly proatherogenic metabolic profile in PsA.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding SLE, data is more limited, but studies have shown increased levels of certain soluble endothelial damage biomarkers, such as ICAM-1 and thrombomodulin (TM) in SLE women and VCAM-1 in patients with lupus nephritis [ 126 , 127 ] Similarly, AS studies indicate that increased levels of ICAM-1, TM and IL-6, as well as increased ADMA serum concentrations are not correlated however with disease activity [ 128 , 129 , 130 ]. In PsA, both ICAM-1 and VCAM-1 levels have been found to be increased compared to controls and ICAM and IL6 were correlated with Cimt [ 131 , 132 ].…”
Section: Immunological Mechanismsmentioning
confidence: 99%